THE EFFECT OF INNOVATION ON CUSTOMER LOYALTY HONDA CBR 150R AT A HONDA DEALER PT. CAPELLA DINAMIK NUSANTARA IN KAMPAR REGENCY - onoadminmaster onoadminmaster (Jurnal Riset Manajemen Indonesia, 2022)
This study aims to find out the effect of innovation on customer loyalty of Honda CBR 150R on Honda PT dealers Capella Dinamik Nusantara in Kampar Regency. The population in this study was all customers who owned a Honda CBR 150R in kampar district. The sample was determined using purposive sampling method with the number of respondents in this study as many as 80 people. Data analysis was done with a simple linear regression model and hypothesis testing was done with t test at alpha 0.05. Based on the results of the research, it was concluded that innovation has a significant effect on customer loyalty of Honda CBR 150R at Honda PT dealers. Capella Dinamik Nusantara in Kampar Regency. The close relationship between Innovation and Customer Loyalty of Honda CBR 150R in Kampar Regency is Very Strong with a correlation coefficient (R) of 77.1%.